Soil and climatic causes of water mains infrastructure bursts - Farewell, Timothy S.; Hallett, Stephen H.; Truckell, Ian G. (Cranfield University, 2012)
Anglian Water plc. have recorded a recent rise in the number of bursts to water mains, impacting on the reportable serviceability of the network to the regulator. Cranfield University National Soil Resources Institute were asked to investigate and advise on potential environmental causes for this. This report Soil and Climatic causes of water mains infrastructure bursts forms a part of the contractual obligations entered into by Cranfield University with Anglian Water plc. and is provided for Anglian Water plc., submitted as a deliverable for Cranfield University project WU33701V as part of the wider Anglian Water plc.  Burst mains and climate factors project.
Keywords: pipe, burst, soil, geohazard, infrastructure